Fungicide Resistance in Botrytis cinerea Populations in California and its Influence on Control of Gray Mold on Stored Mandarin Fruit - Saito, S (Plant disease, 2018)
Gray mold caused by Botrytis cinerea is an emerging postharvest disease affecting stored mandarin fruit in California. To develop effective control programs, fungicide sensitivities to four citrus postharvest fungicides were determined. One hundred B. cinerea isolates each in 2015 and 2016 were obtained from decayed fruit collected within packinghouses and tested for resistance to the fungicides. Sensitivity to azoxystrobin was examined based on the point mutation in the cyt b gene using PCR, while resistance to fludioxonil, pyrimethanil, and thiabendazole was examined on fungicide-amended media. For azoxystrobin, 83 and 98% of the isolates were resistant in 2015 and 2016, respectively. For pyrimethanil, 71 and 93% were resistant in 2015 and 2016, respectively. For thiabendazole, 63 and 68% were resistant in 2015 and 2016, respectively. No fludioxonil resistance was detected in both years. Five fungicide-resistant phenotypes were detected, and the most common phenotype was triple resistance to azoxystrobin, pyrimethanil, and thiabendazole, accounting for 59 and 65% in 2015 and 2016, respectively. Of the 200 B. cinerea isolates, 5, 23.5, and 62% were resistant to one, two, or three classes of fungicides, respectively. Inoculation tests were conducted to evaluate if the fungicides at label rates controlled various resistant phenotypes on fruit. Most fungicides failed to control gray mold on mandarin fruit inoculated with the respective fungicide resistant phenotypes. Our results suggest that alternative control methods need to be integrated into existing decay control programs to target this emerging disease on mandarin fruit